A Study of Integrated Model for Electricity Supply Chain Considering Renewable Energy Fraction and Demand Variation - Takahashi, Kosuke; Sun, Jing (Archives of Business Research, 2023)
This paper aims to derive integrated model for electricity supply chain considering renewable energy fraction and demand variation. Currently, attention is being paid to increasing the ratio of renewable energy generation in the electric power market which called Green Energy Coefficient (GEC). This paper aims to derive an integrated model of electricity supply chain considering renewable energy fraction and demand variation using multi-agent reinforcement learning. The subjects of the models are the consumption market model, the electricity market model, and the production market model. Also, the pricing process in electricity supply chain is analyzed using the proposed multi-agent simulations.